Pengaruh Model Discovery Learning Terhadap Minat Belajar Pendidikan Agama Kristen Siswa Kelas XI SMA Negeri 1 Simanindo Kabupaten Samosir Tahun Pembelajaran 2022/2023 (Jurnal Pendidikan Agama dan Teologi, 2023)
This research aims to determine the positive and significant influence of the Discovery Learning Model on Interest in Learning Christian Religious Education in Class XI Students of SMA Negeri 1 Simanindo Samosir Regency Academic Year 2022/2023. The method used in this research is quantitative descriptive inferential. The results of data analysis show that there is a positive and significant influence between the Discovery Learning Model on Interest in Learning Christian Religious Education in Class the calculated r value > r table is 0.641 > 0.297, thus it is known that there is a positive relationship between variables significant between variables X and Y. 2) Effect test obtained: a) Regression equation test Ŷ=11.15 + 0.65X. b) Test coefficient of determination (r²) = 41%. 3) Test the hypothesis using the F test to obtain F count > F table namely 34.83 > 1.42. Thus Ha is accepted and H0 is rejected.